Sebaran dan Keanekaragaman Ikan Konsumsi pada Ekosistem Terumbu Karang di Teluk Majene, Provinsi Sulawesi Barat - Andi Arham Atjo; Reski Fitriah (Jurnal Airaha, 2020)
The purpose of this research is to find out the type and distribution of fish consumption target in Teluk Majene Prov, west Sulawesi. Coral reef conditions are recorded using segment transect method or Point Intersept Transect (PIT). The transek is stretched according to the predetermined point then a diver performs a dive along the transek 50 meters and recorded on waterproof paper substrates or bentos that are just below the transek line. While the interval distance (point) recording substrates or bentos is every 50 cm ( Hill and Wilkinson, 2004). The categories that observe each point 0.5 m are Hard Coral (HC), Soft Coral (SC), Rubble (R), Dead Coral (DC), Dead Coral Algae (DCA), and Sand (S). The abundance of target fish inhabiting coral reef ecosystems is recorded using the direct census method (Visual Census Method) (English et al.,1994), technically this data collection is done by belt transek method.. The results of this study show that there are 28 types of coral fish that are an important target or consumption in Majene Bay. The most fish species are of the Caesio sp type. As for its distribution, the target fish is found throughout the coral reef ecosystem of Majene Bay. The most distribution is at the location of station 6 precisely in Pasarang Neighborhood, Totoli Village.